An Appraisal of Schoolmasters’ Status in Pre-Modern Muslim Societies - Ayyad, Essam (Islamic Studies, 2023)
Medieval Muslim sources convey two extremely opposing pictures of schoolmasters. Alongside the official, aspirational image of the virtuous providers of knowledge, another subversive stream of literature lampoons them as despicable charlatans (although the main subject they taught was the Qur’ān). This provocative enigma raises many questions and calls for in-depth investigation to clarify its reasons, implications, manifestations, and repercussions. The present article sets out to spell out the dichotomy noted in the sources vis-à-vis the stature of schoolmasters in pre-modern Muslim societies. In particular, it tries to identify the source of this paradox and contextualize the conundrum of a transmitter of sacred knowledge (i.e., the Qur’ān) being ridiculed in a presumably religion-centred community. It also analyses the reasons behind the satires against schoolmasters by notable Muslim informants in medieval times. While so doing, the article tries to give answers and identify nuances concerning a number of related and more inclusive questions.